Financial comparison between rotation forestry (RF) and continuous cover forestry (CCF) on spruce-dominated peatlands - Ahtikoski, Anssi; Siipilehto, Jouni; Repola, Jaakko; Hökkä, Hannu; Lehtonen, Mika; Kärkkäinen, Katri; Hynynen, Jari (Scandinavian Journal of Forest Research)
To date there are no studies comparing RF and CCF on peatlands with stand-level optimization. This study fills this gap and introduces the effect of genetic gain into analyses, covering different locations and two site types on peatlands. Two different data sets are applied: (1) six experimental plots which had been treated by conducting thinnings from below (RF management) and (2) identical locations and site types to those six plots representing bare land cases. A stand-level optimization was applied to achieve maximum net present value according to CCF and RF. The results demonstrated the superiority of RF with genetic gains to other options: RF without genetic gain and CCF when the starting point was an ongoing rotation. The results were valid regardless of location (southern, northern Finland), site type (Vaccinium myrtillus type I, herb-rich) and interest rate (3%, 5%). When starting from a bare land in northern Finland CCF became financially more profitable than RF (with or without genetic gain) with a 5% interest rate. This is mainly due to poorer growth potential in northern compared to southern Finland and the fact that the stand establishment costs associated with RF differ only slightly between southern and northern Finland.